Rethinking Moral Expertise. - Priaulx, Nicky; Weinel, Martin; Wrigley, Anthony (Health Care Analysis, 2016)
The article discusses a study that analyzed the concept of expertise as to moral philosophers. Topics covered include the moral expertise debate on conflation of expertise with the concept of authority, the sociological theory of expertise according to Harry Collins and Robert Evans and the different kinds of competencies and moral expertises. Conclusions indicated that moral philosophers can be included in the group of moral decision-makers as specialist members.